Nurturing information landscapes: Networks, information literacy and the need for a critical phenomenography - Whitworth, Andrew (Proceedings of the International Conference on Networked Learning, 2014)
The aim of this paper is to explore theoretical developments in the field of information literacy (IL), and their relevance to networked learning. The paper is a work of theory, but the implications for practice are not only explored, but are essential to the theoretical point being made. This is that although the promotion of information literacy are essential elements of networked learning, as they are what permit members of the network to create and sustain their own information landscapes, in an autonomous way, there exists in this field a damaging theory-practice gap. Different forms of information literacy exist, which reflect different forms of thinking and approaches to knowledge formation. At the present time, the exploration of variation in IL has best been done by scholars influenced by phenomenography, but this paper argues that this work, valuable though it is, has not as yet dealt properly with the question of authority and how this can be used to retard learning, as well as promote it. The network is identified as a location for learning in which the experience of variation can be best undertaken, but what is required is a critical phenomenography, and concomitant methods for learning that are attuned to the nature of authority and how this can be manifested in information exchanges. This would counter the tendency of modernity to separate intellectual capital from the communities that have created it, imposing the negative effects of cognitive work upon the network while draining off the positive benefits of this work.